Effect of ginger on muscle performance / Megat Haikal Nafis Megat Kamil Azmi, Arif Iskandar Adenan and Ahmad Faiq Anwar Zahanordin - Megat Kamil Azmi, Megat Haikal Nafis; Adenan, Arif Iskandar; Zahanordin, Ahmad Faiq Anwar (2020)
Loss of muscle protein mass and muscle function occurs with increasing age, with risk of physical disability, poor quality of life, and death. Preventative diet, exercise, or treatment may help to improve health span. The most rational approach to delay the progression of muscle loss is based on the combination of proper nutrition, associated with the use of supplements, and a regular exercise program. Zingiber officinale Roscoe Zingiberaceae or ginger contains many phenolic compounds such as gingerol, shogaol and paradol that exhibit antioxidant, anti-tumor and anti-inflammatory properties. Zingiber officinale has been shown to accelerate the recovery of maximal strength following muscle damage suggesting it could be useful in muscle loss prevention. The present study aimed to determine the effect of ginger extract on muscle performance in an animal model.